2021
DOI: 10.1002/jaba.816
|View full text |Cite
|
Sign up to set email alerts
|

There is no such thing as a bad boy: The Circumstances View of problem behavior

Abstract: From the beginning of recorded time human beings have assigned blame to persons who misbehave. The first prominent person to make an alternative case was Father Edward J. Flanagan, the founder of Boys Town, who proclaimed there was "no such thing as a bad boy, only bad environment, bad modeling, and bad teaching" (Oursler & Oursler, 1949, p. 7) in other words, bad circumstances. This paper will refer to this perspective as the Circumstances View of problem behavior and anchor it as the foundational idea for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 57 publications
2
23
0
Order By: Relevance
“…Under the current circumstances, we find it tempting to vilify these people's behavior. We agree with Friman (2021) that, “behavior analysts can be just as prone as non‐behavior analysts to adopt a blame‐laden explanation for problem behavior that occurs outside the specific stimulus control of their training” (p. 6). Yet, their behavior is also a product of circumstances.…”
Section: Some Circumstances Around Sgm People At the Time Rekers And Lovaas (1974) Was Published And Sincesupporting
confidence: 74%
See 2 more Smart Citations
“…Under the current circumstances, we find it tempting to vilify these people's behavior. We agree with Friman (2021) that, “behavior analysts can be just as prone as non‐behavior analysts to adopt a blame‐laden explanation for problem behavior that occurs outside the specific stimulus control of their training” (p. 6). Yet, their behavior is also a product of circumstances.…”
Section: Some Circumstances Around Sgm People At the Time Rekers And Lovaas (1974) Was Published And Sincesupporting
confidence: 74%
“…Here, we take a context‐focused, behavior‐analytic “Circumstances View” (Friman, 2021) of Rekers and Lovaas' (1974) scientific behavior related to this work. One tenet of the Circumstances View is that it applies to the behavior of all people.…”
Section: Some Circumstances Around Sgm People At the Time Rekers And Lovaas (1974) Was Published And Sincementioning
confidence: 99%
See 1 more Smart Citation
“…In whichever area methodologies based upon the science of behavior analysis have been applied, improvements have occurred (cf. Friman, 2021 ). This is exemplified in the thousands of studies that have demonstrated positive outcomes of ABA-based interventions and procedures for autistics/individuals diagnosed with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Behavior analysts' use of a highly rigorous research methodology (i.e., SCED) has led to a science with a strong empirical basis. However, our rigorous yet noticeably boutique approach in isolation has at times adversely affected communication and collaboration (see Friman, 2021). Meta-analyses afford the behavioranalytic community an opportunity to disseminate SCED to those who may be less familiar with the method and behavior analysis alike.…”
Section: Benefits Of Meta-analyses In Appliedmentioning
confidence: 99%